Skeletal Scintigraphy in Assesing the Response of Prostate Cancer Metastases to Androgen Deprivation Therapy - S. P. Mironov; E. I. Vasilenko; P. M. Cholak; V. P. Masenko; M. A. Shariya; D. V. Ustyuzhanin; V. B. Sergienko (Вестник рентгенологии и радиологии)
Androgen deprivation therapy (ADT) with luteinizing hormone-releasing hormone agonists is the basis for drug treatment in patients with metastatic prostate cancer (PC). An accurate assessment of the response of the tumor and its metastases is of primary importance for making a clinical decision regarding the continuation of treatment, changing the line of drugs or the nature of therapy. The presented clinical case illustrates the possibilities of 99mTc-pyrophosphate skeletal scintigraphy for monitoring the response of PC bone metastases to ADT. The efficiency of hormone therapy with Triptorelin has been confirmed by positive changes in the visual and quantitative scintigraphic signs that manifest the metabolic activity of bone tissue in the area of a metastatic lesion. This was manifested by a marked decrease in the intensity of 99mTc-pyrophosphate accumulation in the foci of bone pathology, by a reduction in the number of visualized hot foci, and by a gradual normalization of the scintigraphic pattern. This variant of the metabolic response of bone metastases to ADT correlated with the positive changes in laboratory parameters, as well as with the signs of reversal of the tumor and its metastases, as evidenced by magnetic resonance imaging.